Application of Supply Chain Performance Measurement in Scor Model at Building Project - Mochamad Agung Wibowo; Moh Nur Sholeh (Institut Teknologi Sepuluh Nopember, 2017)
The supply chain has become a priority subject of management research and manufacturing theory in recent years. It has also become an interesting topic in the construction industry. Construction supply chain management is more concerned with the coordination of discrete quantities of materials delivered to a specific construction project. Currently, in some building project, there has been no standard indicators in measuring the performance of the supply chain. Therefore, further research is needed to define the performance indicators there. One of supply chain performance measurement model is Supply Chain Operations Reference (SCOR). The SCOR model provides a unique framework that links performance metrics, processes, best practices, and people into a unified structure. The objective of the study is to define the application of SCOR in construction project. There are 11 Key Performance Indicator (KPI) on the SCOR model that could be used as an supply chain performance indicator in construction project. The research method of this study is by conducting a questionnaire to the project manager and material supplier to determine how the indicators are applied in building projects. The result of the study is the definition of each KPI at building project which facilitates understanding of construction stakeholders to measure the performance of the supply chain.